PENGEMBANGAN MEDIA KOMIK DENGAN MODEL INKUIRI TERBIMBING BERBASIS LITERASI SAINS PADA MATERI SISTEM PEREDARAN DARAH PADA MANUSIA BAGI SISWA KELAS VIII SMP - Lestari, Aulia; Natalina, Mariani; Darmadi, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This research aimed to produce comic media with guided inquiry models based on scientific literacy on circulatory system in humans for grade VIII junior high school students. It had been done in SMPN 4 Pekanbaru and the Faculty of Teacher Training and Biology in University of Riau on April of October 2019. This typeofresearch was a Reseach and Development (R&D) study using the ADDIE model which consists of five stages namely analyze, design, development, implement, and evaluate. This research only reached the development stage by conducting validation by validators and limited trials in stages I and II. The data obtained were analyzed statistically descriptive. The evaluation of the developed comic media includes 6 aspects, namely aspects of comic content, aspects of linguistic / communication, aspects of presentation, aspects of overall appearance, aspects of guided inquiry, and aspects of scientific literacy. The results of the average validationwith a guided inquiry model based on science literacy gained a score of 3.47 in the very valid category. The average results of the limited trial phase I get a score of 96.42% with a very good category and a limited trial phase II get a score of 94.28% with a very good category. Based on these data it can be concluded that the development of comic media with a guided inquiry model based on scientific literacy in the material of the circulatory system in humans for grade VIII junior high school students gets very valid and very good categories so that it is appropriate to be used as a source of learning and can be implemented in the learning process at school.KeyWords: Comic Media, Guided Inquiry, Scientific Literacy, the Material of Circulatory System In Human